Licensing Principles, Consortia and Practical Experiences - Hans Geleijnse (Liber Quarterly: The Journal of European Research Libraries, 1999)
Tilburg University in the Netherlands was the first university in Europe to enter into a license agreement with a publisher. After a year of discussions on technical, organizational and legal issues an agreement was signed between the university and Elsevier Science in December 1993. This agreement covered about 110 Elsevier journals to which the library subscribed. In 1999, Tilburg University Library defined as its goal for the year 2001 to have 50% of its journals available in electronic form and to deliberately move from print to electronic. These goals were set later than expected in 1993.